Fungsi dan Peran Uang Dalam Sistem Moneter Islam - Gausian, Gini; Ayuni, Hilyah Qurrota (STAI Al Musaddadiyah Garut, 2024)
In this era, money is something that cannot be separated from humans in their daily lives. All economic activities require money to move daily goods and services. All goods and services have a price, which in economics can be measured with money. In Islamic economics, money is a medium of exchange and a unit of calculation. However, unlike economic goods and services, money is not a tradable commodity. This article aims to investigate the function and role of money in the Islamic monetary system. This research method leads to a library research by collecting data from various sources such as books, journals, and existing research. The result of this article is that in the Islamic perspective, money is only considered as a means of exchange used to obtain goods and services. Islamic teachings emphasize the rejection of the accumulation of wealth in the form of money and emphasize the prohibition of approaches that make money a commodity object, because the practice of trading money is believed to produce adverse effects, including an increase in the rate of inflation. Keywords: money; monetary system; Islamic economics